Pengaruh Promosi, Kualitass Produk dan Persepsi Harga Terhadap Keputusan Pembelian Tepung Beras Rose Brand: Studi Kasus pada Konsumen Tepung Beras Rose Brand di DKI Jakarta - Ghalib Al Aziz; Kartini Istikomah (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2024)
This research aims to determine the influence of promotion, product quality and price perception on purchasing decisions among consumers of Rosebrand Rice Flour in DKI Jakarta. Type of quantitative research. The population in this study is unknown. The sample used in this research was 97 respondents, with a direct to project sampling system method and using the lemeshow formula. In this research, the data was analyzed using the SPSS version 27 program and Microsoft Excel 2021. The research results showed that simultaneously promotion, product quality and price perception had a significant effect on purchasing decisions. Partially promotion has a significant effect on purchasing decisions, product quality has a significant effect on purchasing decisions, and partially price perception has a significant effect on purchasing decisions.